Can Team Resilience Boost Team Creativity Among Undergraduate Students? A Sequential Mediation Model of Team Creative Efficacy and Team Trust - Fan, Mudan; Cai, Wenjing; Jiang, Lin (Frontiers in Psychology, 2021)
Although recent literature has highlighted the critical role of resilience in creativity literature, existing findings have failed to indicate the processes through which resilience contributes to creativity at the graduate level. The current study fills this gap by hypothesizing the influence of team resilience on team creativity through a sequential mediating mechanism. A time lagged research study was conducted, and a sample of 201 undergraduate students and their teacher filled out questionnaires at three different time points (with 2-week intervals). After aggregating the data at the team level, we employed the PROCESS macro in SPSS to analyze data and test all the hypotheses through performing a sequential mediation analysis. We found that (a) team resilience would predict team creativity; and (b) team efficacy and team trust sequentially mediated the relation between team resilience and team creativity. The results in our study advance the emergent literature on linking resilience and creativity for the practical applications of resilience and creativity in education settings.